Effects of NVP-BEZ235, a dual phosphatidylinositol 3-kinase/mammalian target of rapamycin inhibitor, on HTLV-1-infected T-cell lines - Ishikawa, Chie (Oncol Lett, 2018)
Adult T-cell leukemia (ATL) is an aggressive type of malignancy caused by human T-cell leukemia virus type 1 (HTLV-1). In ATL, the phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) signaling pathway is constitutively active, promoting cell proliferation, survival and chemoresistance. Thus, the PI3K signaling pathway is an attractive therapeutic target for ATL. In the present study, the effects of RAD001 (an mTOR inhibitor), NVP-BKM120 (a pan-PI3K inhibitor) and NVP-BEZ235 (a novel dual PI3K/mTOR inhibitor) on cultured HTLV-1-infected T-cell lines were compared. The results demonstrated that NVP-BEZ235 was more efficacious compared with RAD001 and NVP-BKM120 at inhibiting cell growth. NVP-BEZ235 exhibited cytostatic rather than cytotoxic effects on various HTLV-1-infected T-cell lines, where it induced cell cycle arrest at G(1) phase. NVP-BEZ235 downregulated cyclin D1, cyclin D2, cyclin E, cyclin dependent kinase (CDK)2 and CDK4 expression, and the phosphorylation of retinoblastoma protein. In C.B-17/Icr-severe combined immune deficiency mice implanted with HTLV-1-infected HUT-102 cells, oral NVP-BEZ235 caused marked retardation of tumor growth compared with the control. The present in vitro and in vivo studies highlight the efficacious dual inhibition of PI3K, and mTOR following NVP-BEZ235 treatment. Thus, the results of the current study provide preclinical rationale for phase I clinical studies to examine the effects of NVP-BEZ235 in patients with ATL.